Long-term vemurafenib therapy in advanced melanoma patients: cutaneous toxicity and prognostic implications. (3rd April 2022) - Mandel, Victor Desmond; Medri, Matelda; Manganoni, Ausilia Maria; Pavoni, Laura; De Rosa, Francesco; Ribero, Simone; Foca, Flavia; Andreis, Daniele; Mazzoni, Laura; Magi, Serena; Farnetani, Francesca; Palla, Marco; et al.
Abstract: Background: The introduction of targeted therapies for the treatment of BRAF-mutated metastatic melanoma was associated with different cutaneous adverse events (AEs). Objectives: To describe the type, frequency and severity of cutaneous AEs related to vemurafenib; to understand the association between AEs and vemurafenib efficacy in terms of median overall survival (OS) and median progression-free survival (PFS); to identify molecular characteristics of long-term responders. Methods: This observational, retrospective, monocentric study included all consecutive patients with unresectable stage III or stage IV melanoma and BRAF V600E mutation that started treatment with vemurafenib between May 2012 and May 2014. Results: 62 patients with a median age of 56 years (range 26–82) were enrolled and received vemurafenib for a median period of 7.9 months (range 0.8–63.7). Among them, 45 patients presented at least one skin AE, 12 reduced the dosage due to cutaneous toxicity, and only one firstly reduced and after stopped the therapy. No specific molecular biomarkers were detected in long-term survivors. Conclusions: Among long-term survivors, skin AEs seem to be less frequent and less severe. Results on multivariable analysis revealed that the presence of at least one G2 toxicity is a protective factor considering PFS, but not in terms of OS.